Robotic Duodenojejunostomy for a Rare Case of Acute Idiopathic Superior Mesenteric Artery Syndrome in a Teenage Girl - Planchamp, Thibault; Abbo, Olivier (European Journal of Pediatric Surgery Reports, 2025)
Superior mesenteric artery (SMA) syndrome is a rare cause of proximal bowel obstruction in pediatric surgery. We present the management of a rare, idiopathic, and acute form of SMA syndrome in a teenage girl, successfully treated with a robotic approach. A 14.5-year-old girl with no prior medical history and a normal body mass index (BMI) for her age (18.4 kg/m2) was admitted to our department with acute proximal bowel obstruction syndrome. Initial imaging, including an abdominal X-ray, computed tomography scan, and upper gastrointestinal tract radiography, confirmed the diagnosis of SMA syndrome. Conservative management was initiated with nasogastric tube placement, postural adjustments, and optimal nutritional support. However, symptoms persisted, and surgery was performed 5 months after the initiation of conservative treatment. A robotic-assisted duodenojejunostomy, preserving the fourth portion of the duodenum, was performed without intraoperative complications. Postoperatively, the patient experienced immediate symptom relief and was discharged on postoperative day 4. The postoperative course and long-term follow-up (7 years) were uneventful. This case report describes an acute, idiopathic form of SMA syndrome successfully treated with robotic-assisted duodenojejunostomy in a teenage girl with a normal BMI. To our knowledge, this is only the second reported case of robotic surgery for SMA syndrome in the pediatric literature.
Keywords: superior mesenteric artery syndrome; robotic surgery; pediatric